Evaluation of dalbavancin on length of stay in acute bacterial skin and skin structure infections. Issue 5 (3rd April 2019) - Jones, Bruce M.; Hersey, Roby; Taylor, Colleen; Bland, Christopher M.
Abstract : Purpose: Acute bacterial skin and skin structure infections (ABSSSI) are common reasons for hospital admission. A pathway to shift care to the outpatient setting sooner could decrease length of stay (LOS). Our not‐for‐profit community health system has developed a novel practice of partnering with hospitalists as part of a multidisciplinary early discharge of hospitalized patients with dalbavancin for ABSSSI. The primary purpose of this study was to evaluate outcomes associated with this process. Methods: This was a retrospective evaluation of an ongoing, prospective process between March 2016 and March 2017. The process involves the hospitalist or infectious diseases pharmacist evaluating patients as possible candidates for dalbavancin therapy. Patients were included if their infection was consistent with cellulitis, abscess, or post‐operative wound infection and they received dalbavancin immediately after discharge from the hospital. The primary outcome was hospital LOS with secondary outcomes of direct cost per case and 30‐day readmission rate. Hospital LOS and 30‐day readmission rate were benchmarked to national averages and internal data from the same time frame the year prior. Results: Forty four patients were identified who had received dalbavancin during the time period and met criteria for study inclusion. For the primary outcome of hospital LOS, patients discharged to receive dalbavancin had a mean LOS of 4.3 days similar to published national average (4.95 days in 2011) and lower than internal data (8 days). For secondary outcomes, mean total direct cost per case was $2989 and five patients (11.4%) were readmitted within 30 days similar to published national (16%) and internal data (8.6%). Conclusion: Patients discharged to receive dalbavancin had a LOS and overall 30‐day readmission rate below published national data for ABSSSI. Further study is needed to evaluate this process as an effective means to shorten LOS in the management of ABSSSI.